Deciphering Neuro-Ophthalmic Presentations of Carotid Cavernous Fistulas: A Comprehensive Analysis of Venous Flow Dynamics and Clinical Implications - Ali Al-Shalchy; Ahmed Al-Wassiti; Mohammed Hashim; Mustafa Ismail (مجله كليه طب الكندي)
Background: Carotid cavernous fistulas (CCFs) are abnormal arteriovenous connections between the carotid arterial system and the cavernous sinus, presenting with complex neuro-ophthalmic manifestations due to the redirection of arterial blood into the venous system. This study systematically reviews the diverse neuro-ophthalmic presentations of CCFs, emphasizing the influence of venous flow dynamics.